Post-pandemic behaviour among Indonesian young adults: a mixed-method study on physical activity, dietary patterns, and sleep habits - Rizky Sugianto Putri; Fadhila Inas Pratiwi; Ratna Azis Prasetyo; Citra Hennida (Berita Kedokteran Masyarakat, 2026)
Purpose: This study investigates the post-pandemic habits of Indonesian young adults aged 18 to 23 in Indonesia. It uses a cross-sectional design to evaluate their physical activity levels, dietary patterns, and sleep habits. Methods: A mixed-methods, cross-sectional study used an online questionnaire with quantitative and qualitative data from 260 purposively sampled respondents. Quantitative data were collected and analysed using Spearman’s correlation. The quantitative data comprise three assessments: the International Physical Activity Questionnaire (IPAQ), dietary patterns, and sleep routines. Additionally, qualitative data were gathered through one open-ended question to explore perceived changes in lifestyle habits and were analysed using thematic analysis. Results: A sedentary lifestyle markedly affects various aspects of post-pandemic wellbeing among young adults, with three main changes. Firstly, 80.4% reported exercising fewer than 10 times a month or for less than 150 minutes per week. Secondly, 58.1% preferred ultra-processed foods such as boba drinks, coffee, cereals, tteokbokki, and takoyaki, citing current trends and convenience as influences. Thirdly, 65.4% experienced inadequate sleep, averaging 6-7 hours per night, linked to high screen time. Personal challenges and behavioural shifts post-pandemic were also evident in subjective responses during the transition to what has become the normalised modern lifestyle. Conclusion: Inactivity, poor diet, and lack of sleep emphasise the importance of campaigns encouraging healthier lifestyles among young adults. Tackling these interconnected risks requires coordinated efforts from universities, public health authorities, and policymakers to promote active routines, digital balance, and preventative health strategies for youth.